Developing Recognizing Ability of Hijaiyah Letters Through the Hijaiyah Letter Tree Educational Game Tool at RA Asyarif Sibanggor Jae - Kholilah, Anni; Nur, Kholidah; Mukhlis, Mukhlis (Perkumpulan Peneliti Pendidikan dan Pengembangan Anak, 2024)
Educational game tool Hijaiyah Letter Tree is one of the effective and fun games for children. This study aims to determine: 1) how to make an educational game tool, the educational game tool Hijaiyah Tree game, to recognize Hijaiyah Letters for early childhood at RA As Syarif. To determine the effectiveness of the educational game tool, the Hijaiyah Tree Game, for early childhood at RA As Syarif; 2) Use the tool to recognize Hijaiyah Letters for children at RA As Syarif. This study uses the research and development (R & D) ADDIE development model (Analysis-Design-Develop-Implement-Evaluate) developed by Dickand Carey. Data collection in this study using validator questionnaires, observation sheets, interviews, and documentation. The results of this study obtained an average product validation score by media experts of 3.42, adjusted to the scale four convection table in the range of 3.25 < M ≤ 4.00 with the category